Contribution to the knowledge of Mediterranean lichen-feeding darkling beetles of the genus Stenohelops Reitter, 1922 (Coleoptera: Tenebrionidae) - Nabozhenko, Maxim V.; Mpamnaras, Athanasios; Kalaentzis, Konstantinos (Zootaxa, 2020)
Species of the genus Helopelius Reitter, 1922 (type species: Stenomax aeneipennis Allard, 1876) were known from Rhodes and North Africa. We found that two species described from Rhodes belong to the genus Stenohelops Reitter, 1922, and Helopelius can be interpreted as a subgenus within latter, guided by the article 23.2 of ICZN. The following synonyms are proposed: Helopelius, stat. n. (from genus to subgenus) = Stenomaleis Español, 1957, syn. n.; Stenohelops Reitter, 1922 = Gunarellus Reitter, 1922, syn. n.; Stenohelops (Helopelius) aeneipennis (Allard, 1876) = Helopelius disgregus Reitter, 1922, syn. n., = Gunarus gayirbegi Nabozhenko & Keskin, 2009, syn. n. As a result, the following species are transferred from the former genus Helopelius to the genus Stenohelops: Stenohelops (Helopelius) nodifer (Kraatz, 1880), comb. n.; Stenohelops (Helopelius) otini (Antoine, 1949), comb. n.; Stenohelops (Helopelius) subsinuatus (Antoine, 1951), comb. n.; Stenohelops (Helopelius) verrucosus (Vauloger de Beaupré, 1900), comb. n.; Stenohelops (Helopelius) zaianus (Antoine, 1949), comb. n. Thus, the subgenus Helopelius contains 11 species from three isolated geographical exclaves: Western Mediterranean, Eastern Mediterranean and China. Lectotypes of Stenomax aeneipennis Allard, 1876, Helops gratus J. Frivaldszky, 1894 and Cylindrinotus (Helopelius) disgregus Reitter, 1922 are designated. Data on fossil species of the genus and the allied extinct taxa, as well as on bionomics of extant species of the subgenus Helopelius are presented. The check-list for extant and extinct species of Stenohelops is given.